INTEGRATING CLIMATE CHANGE INTO CONSERVATION PLANNING FOR TAXUSCHINENSIS, AN ENDANGERED ENDEMIC TREE PLANT IN CHINA - Chun-Jing Wang; Ji-Zhong Wan; Zhi-Xiang Zhang; Liang-Cheng Zhao (Journal of Animal and Plant Sciences, 2017)
Climate change has the potential to severely threaten Taxuschinensis, an endangered endemic tree plant in China. Hence, we need to plan conservation areas for T. chinensis in light of climate change. We applied the common species distribution modelling software Maxent to generate maps of current and projected future distributions of T. chinensis. These distributional maps with conservation planning software were used to determine priority protection areas (PPAs). Then, we evaluated the ability of existing nature reserves to conserve T. chinensis and performed a gap analysis for the species under climate change. The PPAs of T. chinensis were mainly distributed within central and southern China. Nature reserves such as Zhangjiajiedani, Yangzie, Wolong, Baishuijiang and Dabashan have the greatest potential to protect T. chinensis under climate change. In situ and ex situ conservation of T. chinensis in the PPAs of these five nature reserves should be a priority. However, existing nature reserves lag far behind the PPAs with respect to total area. Therefore, more nature reserves are urgently needed for species like T. chinensis to cope with rapid climate change. Meanwhile, we should strengthen protection and management of areas that will experience an increase in T. chinensis while enhancing both monitoring and protection activities for T. chinensis in PPAs that are predicted to experience decreases in population size. Finally, we suggest that climate change must be integrated into conservation planning for the endangered plant species, T. chinensis.
Keywords: climate change; conservation management; nature reserves; species distribution modelling; Taxuschinensis